Çankırı Redı?f Battalion in the First Balkan War (1912-1913) - Ateş, Oral; Bazna, Alperen Yalçın (Fırat University, 2026)
In this study, the establishment of the Çankırı Redif Battalion since the campaign of the Balkan War, its transfer to the campaign duty station and its battles have been analyzed in detail, findings that have not been unearthed to date have been identified and important contributions have been made to Turkish military history. Within the scope of the research, military archive documents as primary sources, printed works, periodicals and memoirs as secondary sources were examined and a scientific conclusion was reached. It was determined that the 867-strong Çankırı Redif Battalion, which set out within 10 days following the announcement of mobilization, was one of the rare units that completed its organization in this short time and became ready for duty. In addition, soldiers who reached the level of martyrdom in the battles but were not included in the records of the Ministry of National Defense were identified and included in the literature. In the context of the process of forming redif units in the Ottoman Empire, it was determined that the elders of Çankırı Sancak demanded that a redif battalion and a cavalry company be organized in Çankırı and that they notified the Ankara Müşirlik in this direction. Within this framework, it was determined that the construction of the barracks was completed with the contributions of the local notables. As one of the cities that gave the highest number of martyrs and veterans in proportion to its population, Çankırı once again showed its loyalty to its homeland and state by preparing in a short time during the Balkan War mobilization process. In addition to making an innovative contribution to the literature in terms of improving the historiography of the Balkan War, this example study will also be a reference source for future studies on the 502 redif battalions campaigned from all over the Ottoman region during the Balkan War.

Bu çalışmada, Çankırı Redif Taburu’nun Balkan Savaşı seferberliğinden itibaren kuruluşu, sefer görev yerine intikali ve muharebeleri detaylı bir şekilde analiz edilerek bugüne kadar gün yüzüne çıkarılamayan bulgular tespit edilmiş ve Türk askerî tarihine önemli katkılar sağlanmıştır. Araştırma kapsamında birincil kaynak olarak askerî arşiv belgeleri, ikincil kaynak olarak basılı eserler, süreli yayınlar ve hatıratlar incelenerek sonuca ulaşılmıştır. Seferberlik ilanını takiben 10 gün içinde yola çıkan 867 kişilik Çankırı Redif Taburu’nun, bu kısa sürede teşkilatlanmasını tamamlayarak göreve hazır hale gelen nadir birliklerden biri olduğu tespit edilmiştir. Ayrıca muharebelerde şehit mertebesine ulaşan ancak Millî Savunma Bakanlığı kayıtlarında yer almayan askerler belirlenerek literatüre kazandırılmıştır. Osmanlı Devleti’nde redif birlikleri oluşturulması süreci bağlamında Çankırı Sancağının ileri gelenlerinin bir redif taburu ve süvari bölüğünün Çankırı’da teşkil edilmesini talep ettikleri ve bu doğrultuda Ankara Müşirliğine bildirimde bulundukları belirlenmiştir. Bu çerçevede kışla inşasının mahalli eşrafın katkılarıyla tamamlandığı tespit edilmiştir. Çankırı, nüfusuna oranla en çok şehit ve gazi veren şehirlerden biri olarak Balkan Savaşı seferberliği sürecinde de kısa sürede hazırlanmasıyla vatanına, devletine bağlılığını bir kez daha göstermiştir. Bu örnek çalışma, Balkan Savaşı tarih yazımının geliştirilmesi açısından literatüre yenilikçi bir katkı sunmasının yanında, Balkan Savaşı’nda Osmanlı coğrafyasının dört bir yanından seferber edilen 502 redif taburu ile ilgili yapılacak çalışmalara da referans kaynak olacaktır.
I. Balkan Savaşı’nda Çankırı Redif Taburu (1912-1913)
Keywords: History of The Republic of Turkiye; Türkiye Cumhuriyeti Tarihi; Ataturk's Principles History of Revolution; Atatürk İlkeleri İnkılap Tarihi; Late Modern Military History; Yakınçağ Askeri Tarih